Measurement of skin viscoelasticity: A non‑invasive approach in allergic contact dermatitis - Constantin, Maria-Magdalena; Bucur, Stefana; Serban, Elena-Daniela; Olteanu, Rodica; Bratu, Ovidiu; Constantin, Traian (Experimental and therapeutic medicine, 2020)
Non-invasive bioengineering technologies are constantly being developed, as they can provide useful insights and contribute to the improvement of medical care and scientific education. The purpose of this study was to assess skin viscoelasticity using the suction chamber method in patients with allergic contact dermatitis vs. healthy subjects, before and after applying a moisturizer safety testing cream. This was a prospective controlled study over a 3-year period (March 2016-March 2019), with 81 subjects being divided in two balanced groups: Patients with allergic contact dermatitis and healthy subjects, respectively. The skin viscoelasticity was determined for all subjects with Cutometer[R], using the suction method, by performing a dynamic assessment of parameters before and after applying a moisturizing cream. The results indicate a decrease in the elasticity parameters in both groups, indicating an improvement of the elastic properties under the treatment. Skin capacity to return to its previous form after the deformation, i.e., pure elasticity and biological elasticity, showed overall elevated values in the group with contact dermatitis, demonstrating the efficacy of the emollient cream after applying it for 28 days (increase by 11.7 and 4.9% respectively, compared with baseline, when patients had dry, untreated skin). However, in healthy subjects, these parameters do not achieve important values, but they remain rather stable over time with a very slight improvement (6.6% after 28 days). The Cutometer is an easy to use, efficient and widely used instrument for measurements in studies that perform a quantitative assessment of the effectiveness of different formulations intended for application on the skin. Key words: cutometer, skin barrier, viscoelasticity, safety testing, formulation, allergic contact dermatitis